IMPLEMENTASI RUANG PUBLIK TERPADU RAMAH ANAK (RPTRA) DI RPTRA SUNTER JAYA BERSERI, KELURAHAN SUNTER JAYA, JAKARTA UTARA - dara, andi; idrus, iqbal (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2019)
This research was aimed to analyzed how The Implementation of Integrated Child Friendly Public Space (ICFPS) in ICFPS Sunter Jaya Berseri, Kelurahan Sunter Jaya, North Jakarta. In this study researcher used the theory of implementation from Jones (1991) which consist the pillars of the organization, interpretation, and application. The method used is method qualitative. The results of the study concluded that The Implementation of the program Integrated Child Friendly Public Space (ICFPS) in ICFPS Sunter Jaya Berseri, Kelurahan Sunter Jaya, North Jakarta it is optimal even though there is still a little deficiency. On the dimension of the organization for the arrangement of the establishment of the institutions, the availability of human resources, and the allocation of funds/budget has been sufficient. On the dimension of the interpretation for understanding implementor, elite support, public support, and guidelines had been good enough. On the dimension of application for the monitoring and evaluation as well as the socialization of the program is good even though there are still some people feel short in terms of the existing facilities and not appropriate the area of the field as expected, but people still feel the benefits other than Integrated Child Friendly Public Space (ICFPS). As input to all parties to the tribe department associated with Integrated Child Friendly Public Space (ICFPS) can help in fixing some flaws in Integrated Child Friendly Public Space (ICFPS) Sunter Jaya Berseri.